Gender minorities at music festivals - Kinnunen, Maarit; Honkanen, Antti (Emerald Publishing Limited, 2025)
Purpose – The purpose was to examine the prevalence and type of inappropriate behaviour gender minorities face and how they perceive such behaviour. The study is framed within Gidley et al.’s social inclusion model, indicating areas where actions are needed to avoid social exclusion.
Design/methodology/approach – The research data comprised over 12,000 responses to a web survey, which included 184 responses from gender minority members and four in-depth, semi-structured interviews. The data were analysed using statistical methods and interpretative phenomenological analysis.
Findings – About 59% of gender minority members had experienced inappropriate behaviour, compared to 34%offemalefestivalattendees. Themostcommonformofinappropriatebehaviourtowardsgenderminorities was harassment because of gender, followed by sexual harassment, physically threatening situations and harassment because of appearance or clothing. Interviews were analysed against the theoretical framework of social inclusion, determining how the experiences influenced access, participation and empowerment.
Practical implications – Festivals must have unisex toilets. Safer space policies should be better communicated, more visible and more practical. Instead of having one harassment contact person, there should be a whole team. Training the festival personnel, particularly the security staff, is highly important. People are reluctant to report problems to the security personnel since those personnel might be part of the problem. There should be members of gender minorities among performers, workers, security staff and volunteers.
Originality/value – Studies on inappropriate behaviour at festivals have concentrated on female experiences of sexual harassment. Gender minorities have hardly been studied, even though they face more inappropriate behaviour than any other minority group. Furthermore, gender minorities are typically grouped with sexual minorities even though their experiences differ from one another. We applied Gidley et al.’s hierarchical model of social inclusion to gender minority members in the context of music festivals. In doing so, we added knowledge of attitudes and practices that reduce and endanger feelings of access, participation and empowerment.